Increased serum sialic acid levels in primary Osteoarthritis and inactive rheumatoid arthritis - ALTURFAN, EBRU IŞIK (TOHOKU UNIV MEDICAL PRESS, 2007)
ALTURFAN, A.A., USLU, E., ALTURFAN, E.E., HATEMI, G., FRESKO, I. and KOKOGLU, E. Increased Serum Sialic Acid Levels in Primary Osteoarthritis and Inactive Rheumatoid Arthritis. Tohoku J. Exp. Med., 2007, 213 (3), 241-248 - Accumulation of oxidized proteins and impaired antioxidant system have been shown to be associated with arthritis. Serum sialic acid (SA) is known as a parameter of inflammation. In the present study, to explore the potential role of SA in arthritis, we measured serum SA levels, plasma protein oxidation, and antioxidant status in patients with primary osteoarthritis (POA) and inactive rheumatoid arthritis (RA). Inactive RA (iRA) was defined upon the American College of Rheumatology criteria for clinical remission of RA. A total of 40 patients (20 POA patients, including 4 male subjects, and 20 iRA female patients) and 20 healthy female subjects were included in this study. SA, antioxidants, and protein oxidation levels were determined spectrophotometrically in serum or plasma samples. Serum SA levels were significantly increased in POA (3.34 +/- 0.37 mM, p < 0.0001) and 1RA (3.11 +/- 0.47 mM, p < 0.05), compared with healthy controls (2.41 +/- 0.16 mM). Plasma total antioxidant activity, plasma superoxide dismutase activity and serum reduced glutathione levels were significantly decreased in patients with POA and those with iRA, whereas plasma carbonyl content and serum total protein were increased in those patients. Moreover, plasma total thiol levels were significantly increased in iRA and decreased in POA. Thus, increased SA and protein oxidation levels are associated with the decreased antioxidant levels in POA and iRA patients. These results suggest that SA may be considered as a potent defense molecule against oxidative damage in arthritis. Antioxidant therapy may halt or ameliorate the progression of arthritis. - osteoarthritis; rheumatoid arthritis; oxidative stress; antioxidants; sialic acid (c) 2007 Tohoku University Medical Press.
Keywords: PROTEIN CARBONYL GROUPS; LIPID-PEROXIDATION; SYNOVIAL-FLUID; ANTIOXIDANT CAPACITY; REACTIVE OXYGEN; NITRIC-OXIDE; PATHOGENESIS; BIOMARKERS; OXIDATION; CRITERIA